Form Over Substance? Ineffectiveness of Good Corporate Governance in Family-Controlled Firms - Yuliani; Eddy Suratman; Giriati (Inovasi Analisis Data, 2026)
Purpose — This study examines whether family ownership concentration explains why Good Corporate Governance (GCG) mechanisms may fail to improve financial performance in listed non-financial firms operating within a concentrated-ownership environment. Design/methodology/approach — Using panel data, ultimate family ownership is classified through an internationally established voting rights threshold. Interaction models assess whether family control alters the relationship between formal governance structures and accounting performance, with alternative specifications and robustness procedures used to evaluate the stability of the results. Findings — Formal governance compliance has no significant direct relationship with financial performance, and this finding remains stable across alternative specifications. The moderating role of family ownership is directionally consistent with a weakening effect but is not robustly significant. Family-controlled firms also exhibit substantially weaker formal governance structures than non-family firms without a corresponding performance penalty. Originality/value — This study integrates principal–principal agency theory with institutional decoupling theory to explain why formal oversight mechanisms may remain detached from substantive control in concentrated-ownership markets. Its population-level classification of ultimate ownership extends the “form over substance” thesis from a family-firm-specific phenomenon to a systemic characteristic of governance regimes dominated by controlling shareholders.